ANALISA PENGGUNAAN E-COMMERCE SHOPEE PADA MASA PANDEMI COVID-19 MENGGUNAKAN MODEL UTAUT - Susanna Prety Wantri Ndruma; Irfan Mahendra (UPT Penerbitan Universitas Jember, 2022)
During the Covid-19 pandemic, the use of e-commerce increased very significantly, including Shopee. Order to evaluate how the level of use of e-commerce applications during the pandemic, can be measured using the Unified Theory of Acceptance and Use of Technology (UTAUT) Model. This study aims to analyze the use of Shopee's E-commerce during the Covid-19 pandemic using the Unified Theory Of Acceptance and Use of Technology (UTAUT) Model. This study discusses the effect of performance expectancy, effort expectancy, social influence, and facilitating conditions on behavioral intentions. The method of data collection was carried out using a questionnaire. The results showed that partially there was one variable that was rejected, namely the social influence variable. Meanwhile, the variables of performance expectations, effort expectations, and facilitation conditions have a significant effect on behavioral intentions. However, it simultaneously shows that all variables have a positive and significant effect on behavioral intention. Keywords: behavioral intention, covid-19, e-commerce, UTAUT